Preventing Child Sexual Abuse Skills Of Parents: Literature Review - Solehati, Tetti; Diana Maljuliani; Nasya Yuniar; Chealse Fernanda; Venturini; Nabila Fauziah Nur` Aini; Olivia Qashrina Agni Putri M; Yanti Hermayanti; Cecep Eli Kosasih; Henny Suzana Mediana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Introduction: Child sexual abuse (CSA) can negatively impact children’s physical, psychological, and social impacts. Parents are responsible for preventing children from becoming victims of CSA. Unfortunately, many parents do not have good skills or behavior, so they are at risk of increasing the incidence of child sexual abuse. Objective: This study aims to explore parental skills in preventing child sexual abuse. Methods: This study was conducted using the literature review method, using the CINAHL, Science Direct, Pubmed and Proquest databases. Articles were screened using inclusion criteria published in 2010-2020, full text, in English, quasi-experimental research design, Randomized Controlled Trial, and Clinical Trial. It was found that five articles were selected after an assessment using JBI (Joanna Briggs Institute). Results: Parents’ skills or behavior in prevented child sexual abuse, including teached self-protection skills and handling steps in the event of sexual abuse, establishing good communication, providing education related to sexual abuse prevention, discussing sexual abuse, and providing a more favorable safe environment , such as child supervision and parenting skills. Some of these were skills that influence the prevention of CSA. But from various studies, it was found that the parental skills were low in preventing CSA. Conclusion: It is found that parents’ skills are lack in preventing CSA, because in general parents only take part of the preventive measures for CSA. Suggestion: The need for interventions to increase the knowledge, attitudes, awareness and motivation of parents in preventing child sexual abuse.